High‐precision mathematical modelling of passive intermodulation in connectors - Menglin Song; Qiuyan Jin (Electronics Letters, 2022)
Abstract Passive intermodulation is an undesirable but unavoidable interference in communication system. Two high‐precision mathematical models are proposed to predict the passive intermodulation behaviour in coaxial connectors. Three kinds of coaxial connectors are selected as test samples. A series of two‐tone tests with increasing input power from 30 to 44 dBm are performed. The measured results are divided into two parts, which are used for model fitting and prediction verification, respectively. Based on the observation of the concave function characteristics in current‐voltage curve of the connectors, the hyperbolic sinusoidal (sinh) and Gram‐Charlier A Series models are proposed. Compared with the polynomial models, the goodness of fit of the two novel models is higher. Model validation is performed, showing the higher accuracy of the proposed models.